Trust in organization and Self-Efficacys’s relation with upward influence tactics - Kütük, Cem (My University, 2006)
unknown
Keywords: Etkileme Taktikleri; İkna; Örgütsel Yönetim; Öz-Yeterlilik İnancı; Politik Davranış